Penerapan Model Pembelajaran (Webbed) Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran IPS (Universitas PGRI Sumatera Barat, 2022)
The purpose of this study was to analyze the application of the webbed learning model to the learning outcomes of students in social studies subject class VIII.2 at SMP N 7 Pariaman. The results of the application of the learning model (webbed, teacher preparation before the application of the webbed model (1) the teacher prepares (RPP) using the webbed model (2) the teacher determines the theme (3) the teacher divides the students into group discussions (4) the teacher prepares the media. Webbed Learning Model at the first meeting the teacher begins (KBM) by greeting, praying and checking student attendance, core activities (1) determine the theme, (2) design learning, (3) connect all activities. Stages of student implementation, culmination stage After that, draw conclusions, so from the results of the tests used there were 25 students (86%) learning outcomes of students in the good category who completed reaching the KKM, namely, 72 there was a significant effect of the application of the webbed learning model on student learning outcomes.